Overview of PCTK3/CDK18: A Cyclin-Dependent Kinase Involved in Specific Functions in Post-Mitotic Cells - de Oliveira Pepino, Rebeka; Coelho, Fernanda; Janku, Tatiane A. B.; Alencar, Diandra P.; de Azevedo, Walter Figueira; Canduri, Fernanda (Current Medicinal Chemistry, 2021)
Cyclin-dependent kinases (CDKs) comprise a family of about 20 serine/threonine kinases whose catalytic activity requires a regulatory subunit known as cyclin; these enzymes play several roles in the cell cycle and transcription. PCTAIRE kinases (PCTKs) are a CDK subfamily, characterized by serine to cysteine mutation in the consensus PSTAIRE motif, involved in binding to the cyclin. One member of this class is PCTK3, which has two isoforms (a and b) and is also known as CDK18. After being activated by cyclin A2 or phosphorylation at Ser12 by PKA, PCTK3 can perform several functions. Among these functions, we may highlight the following: modulation of cargo transport in membrane traffic, p53-responsive gene, regulation of genome integrity. According to different studies, PCTK3 dysfunction is related to a wide range of diseases, such as metabolic diseases, cerebral ischemia, depression, cancer, neurological disorders, and Alzheimer's disease. Although this protein participates in different biological events, we may say that PCTK3 has received far less attention than other CDKs. There are thousands of published articles about other CDKs and less than two hundred articles related to PCTK3. The main objective of this review is to present the selected published studies about this protein. Our focus is on PCTK3 particularities compared to other CDKs. Here we give an overview of the biological functions of PCTK3 and explore its potential as a target for drug design.
Keywords: PCTK3